Leadership in Psychiatry – Enhancing Practice in the Indian Context - Pallavi Hoskote; Satish Ramaiah (Journal of Psychiatry Spectrum)
Leadership skills are essential in healthcare, especially in the field of psychiatry. India, being a middle-income nation, has seen major transformations both in the private and public health care sectors. Specifically, mental health is witnessing a phenomenal change with the advent of new technological advancements, growing public awareness, implementation of new Mental Healthcare Act (2017) and increasing investments into setting up world class services. This article represents our viewpoint with current existing challenges for psychiatrists and the field of psychiatric practice in the Indian context; potential of leadership with respect to practice of psychiatry; working towards change; patient and organizational benefits of leadership; influence of leadership on personal growth and practice; vision for the future; transformational leadership as the way forward and recommendation to include leadership skills training with the academic psychiatry training.